Utilization of Health Consultation Application (Chat Dokter Online) for COVID-19 Self-Isolation Patient Services in Palembang City - Rachmat Hidayat; Patricia Wulandari (Indonesian Community Empowerment Journal, 2021)
Chat Dokter Online is a digital health platform developed by CV Cattleya Consultation Center based in Palembang. This digital health platform serves general public health consultations regarding health problems both in the city of Palembang and from outside the city of Palembang. This application is expected to be able to provide optimal services and a broad reach for users and especially patients who are self-isolating COVID-19 in Palembang City. The implementation of this community service activity is carried out through the stages of observation, interviews, application prototype development, application testing, application utilization, and monitoring application utilization. Chat Dokter Online provides massive health services and easy access for patients exposed to COVID 19 to determine the clinical degree of COVID-19, complaints felt by patients and to determine when to finish self-isolation. In addition, this application helps the public to get valid health information directly from doctors and experts.